Perkembangan Rumah Sakit Umum Daerah Lubuk Basung (1986-2020) - Iqbal, Muhammad; Najmi, Najmi (Jurnal Kronologi, 2023)
This thesis examines the development of Lubuk Basung Regional General Hospital from 1986-2020. The purpose of writing this thesis describes the developments and changes that occurred at Lubuk Basung Hospital as the only C-level Health Service unit in Agam district from 1986-2020.To be more focused, this research is focused on the following problem formulations: (1). What is the background of the establishment of Lubuk Basung Hospital?, (2). How is the Development of Health Services at Lubuk Basung Hospital (1986-2020)? The Research Methods used are; Heuristics is the first stage carried out to find sources relevant to research. Source criticism is a form of process carried out by the author to find and filter the truth value of sources, Interpretation is a stage where researchers try to express various ideas of their thoughts obtained through primary or secondary sources, Historiography is the last stage in the Historical method where in this stage the author writes the results of research chronologically and systematically. The results of this study illustrate that the development and changes in the institution of Lubuk Basung Regional General Hospital continue to experience progress from 1986 to 2020. Especially when it started when the Hospital was designated as a Regional General Hospital with type D class and changed to a Regional General Hospital with type C class to its role in providing services for the people of Lubuk Basung which is still standing today